2013
DOI: 10.5152/jtgga.2013.09471
|View full text |Cite
|
Sign up to set email alerts
|

Relation between single serum progesterone assay and viability of the first trimester pregnancy

Abstract: This study was designed to detect the relation between serum progesterone and viability of pregnancy during the first trimester. Prospective study carried out in Al-Rashid Maternity and Ahmadi Kuwait oil company hospitals, over three years from February 2009 to February 2012. Two hundred and Sixty (260) pregnant women were hospitalized due to vaginal bleeding and/or abdominal pain during the first trimester of their pregnancies and were included in this study. Women included in this study were; sure of dates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…The combined cut-off value of progesterone >25.2 ng/mL and β-hCG >126.5 mIU/mL may suggest a good prognosis. 19 Similar findings were seen in studies conducted by Abdelazim IA et al 20…”
Section: Discussionsupporting
confidence: 85%
“…The combined cut-off value of progesterone >25.2 ng/mL and β-hCG >126.5 mIU/mL may suggest a good prognosis. 19 Similar findings were seen in studies conducted by Abdelazim IA et al 20…”
Section: Discussionsupporting
confidence: 85%
“…The Royal College of Obstetricians and Gynaecologists' guideline stated that the value of single serum progesterone in early pregnancy is useful for predicting the outcome of pregnancy, and when serum progesterone threshold is 20 nmol/L (about 6.2 ng/mL), it can be predicted non-viable pregnancies with 93% sensitivity, 94% specificity in symptomatic pregnant (22). In the study of Abdelazim et al when the serum progesterone cut-off level was 10 ng/ml, it was 79.3% sensitive for non-viable pregnancy diagnosis, 93.3% specific for viable pregnancy diagnosis; when serum progesterone cut-off level was 20 ng/ml, it was 95.1% sensitive for non-viable pregnancy diagnosis and 98.9% specific for viable pregnancy diagnosis (23). Elson et al reported that the 25 ng/mL serum progesterone cut-off value obtained by ROC curve statistical analysis predicts viable pregnancies with 100% sensitivity and 43% specificity (5).…”
Section: Discussionmentioning
confidence: 97%
“…The importance of first trimester value of progesterone, which is necessary for preparation of the endometrium for implantation, support of decidualization required for a healthy maintenance of pregnancy, and development of immune tolerance against the fetus, has been shown in several studies on both single and multiple pregnancies. [1][2][3] In some studies emphasizing the role of progesterone in predicting gestational prognosis in early pregnancy, maternal progesterone level below 35 nmol/L (11 ng/mL equivalent) has been found to be associated with vaginal bleeding and miscarriage. [4,5] However, there are also studies stating different progesterone threshold values for healthy maintenance of pregnancy in the first trimester.…”
Section: Introductionmentioning
confidence: 99%